The poetic image in the notice of Shawky Bzeih - Suwaidan, Faisal; Fadel , Haider (Al-Adab Journal, 2024)
The research deals with the role of the poetic image in the formation of the connotations within the poetic text of the poet Shawqi Bzaig, as the words move away from their lexical connotations to new connotations that contribute to giving the text its unique identity. The research aims to stand on the stylistic structures employed by the poet in constructing poetic images such as imagination, myths, symbols, and the combination of contradictions, which gives the text the ability to renew through the inspiration produced by each new reading of the text.